Developing a Global Strategy for the Control of Folate Deficiency and Folic Acid Responsive Neural Tube Defects in Low- and Middle-Income Countries (P10-107-19). (13th June 2019) - Martinez, Homero; Poulin, Jessica; Weakland, Aliki; Bailey, Lynn; Mehta, Rajesh; Afidra, Ronald; Brown, Kenneth
Abstract: Objectives: To develop a global action plan for the control of folate deficiency and folic acid responsive neural tube defects (anencephaly and spina bifida) Methods: Establish a multi- and inter-disciplinary group to develop a global action plan for folate-sensitive NTD prevention Ensure regional lab capacity exists to assess folate status applying a harmonized microbiologic assay (MBA) to measure red blood cell (RBC) folate, establishing a global network of regional laboratories coordinated by an umbrella organization Promote improvements of folate status in women of reproductive age (WRA) in LMIC, engaging a wide variety of national and global stakeholders Address key knowledge gaps related to the prevention of folate sensitive NTDs Improve knowledge availability and sharing amongst global stakeholders in NTD prevention Communicate and share the work of the Folate Task Team Results: A standing Folate Task Team comprised of a 2-member Secretariat, a 10-member Expert Advisory Group, 4 Ex-Officio members, and 4 "As Needed" advisors (see Fig. 1) Identification of an initial list of 12 global stakeholders and partner organizations Five resource laboratories have been trained at the Division of Laboratory Sciences - CDC, including labs in Vietnam, Sri Lanka, Philippines, Tanzania, and Pakistan A training video supported by a manual and mini posters to illustrate specific activities of the assay has been produced by CDC. A landscaping analysis has identified countries that have mandatory/voluntary food fortification practices, information on folate status in the population, burden of NTDs, and consumption patterns of fortified foods Identification of alternative foods/food vehicles likely to be fortified to reach at-risk segments of WRA Dissemination activities are shared at https://www.nutritionintl. org/what-we-do/nteam/folate-task-team/ Conclusions: The estimated global prevalence of NTD-affected pregnancies is estimated to be 260, 100 in 2015 and has a significant emotional and economic impact on families and society, while contributing to the loss of human potential for countries The global action provides a clear path forward to help direct and prioritize investments, advance resource mobilization, and garner the political will to accelerate NTD prevention in LMIC Funding Sources: The Bill & Melinda Gates Foundation. Supporting Tables, Images and/or Graphs: